COMPARISON BETWEEN GRINDING AND LAPPING OF MACHINED PART SURFACE ROUGHNESS IN MICRO AND NANO SCALE - W.M., Shewakh, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Micro and Nano surface finish has become an important parameter in semiconductor, optical, electrical and mechanical industries. In this work a comparison between two traditional finishing processes grinding and lapping was made. Machined parts surface roughness in micro and nano scale has been measured using two different devises in two different directions normal and perpendicular to the machining direction. Results show that the traditional finishing processes are not suitable for nano scale surface finish. There is a significant difference between the normal and perpendicular measured surface roughness in nano and micro scale.